Effects of precooling on endurance exercise performance in the heat: A systematic review and meta-analysis of randomized controlled trials - Yu, L.; Chen, Z.; Wu, W.; Xu, X.; Lv, Y.; Li, C. (Nutrients, 2024)
An increasing number of studies have explored the effects of precooling on endurance exercise performance in the heat, yet the available results remain inconsistent. Therefore, this study aimed to investigate the effects of different precooling strategies on endurance exercise performance in the heat. A comprehensive search was conducted across PubMed, Web of Science, Cochrane, Scopus, and EBSCO database. The Cochrane risk assessment tool was employed to evaluate the methodological quality of the included studies. A meta-analysis was subsequently conducted to quantify the standardized mean difference (SMD) and 95% confidence interval for the effects of precooling on endurance exercise performance in the heat. Out of the initially identified 6982 search records, 15 studies were deemed eligible for meta-analysis. Our results showed that precooling significantly improved time trial (TT) performance (SMD, -0.37, p < 0.01, I2 = 0%) and time to exhaustion (TTE) performance in the heat (SMD, 0.73, p < 0.01, I2 = 50%). Further subgroup analyses revealed that external precooling is more effective in improving TT performance (SMD, -0.43, p = 0.004, I2 = 0%) and TTE performance (SMD, 1.01, p < 0.001, I2 = 48%), particularly in running-based performances (TT, SMD, -0.41, p = 0.02, I2 = 0%; TTE, SMD, 0.85, p = 0.0001, I2 = 31%). Precooling is an effective approach to improve endurance exercise performance in the heat. External precooling is more effective in improving endurance exercise performance, particularly in running-based performance.